2012
DOI: 10.1161/circulationaha.111.064873
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Changes in Resuscitation Practice on Survival and Neurological Outcome After Out-of-Hospital Cardiac Arrest Resulting From Nonshockable Arrhythmias

Abstract: Background-Out-of-hospital cardiac arrest (OHCA) claims millions of lives worldwide each year. OHCA survival from shockable arrhythmias (ventricular fibrillation/tachycardia) improved in several communities after implementation of American Heart Association resuscitation guidelines that eliminated "stacked" shocks and emphasized chest compressions. "Nonshockable" rhythms are now the predominant presentation of OHCA; the benefit of such treatments on nonshockable rhythms is uncertain. Methods and Results-We stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 33 publications
(44 reference statements)
0
54
2
5
Order By: Relevance
“…Es ist allgemein anerkannt, dass Ersthelfer-CPR für das Überleben von Kreislaufstillständen außerhalb des Krankenhauses entscheidend ist. Thoraxkompressionen und frühe Defibrillation sind die Hauptdeterminanten des Überlebens beim außerklinischen Kreislaufstillstand, und es gibt Hinweise, dass sich mit Einführung von Laientrainings das 30-Tageund 1-Jahres-Überleben verbessert hat [8,9]. Aus diesen Gründen ist das primä-re Ziel der Reanimationsausbildung das Training von Laien in CPR.…”
Section: Trainingsstrategien Für Die Basismaßnahmenunclassified
“…Es ist allgemein anerkannt, dass Ersthelfer-CPR für das Überleben von Kreislaufstillständen außerhalb des Krankenhauses entscheidend ist. Thoraxkompressionen und frühe Defibrillation sind die Hauptdeterminanten des Überlebens beim außerklinischen Kreislaufstillstand, und es gibt Hinweise, dass sich mit Einführung von Laientrainings das 30-Tageund 1-Jahres-Überleben verbessert hat [8,9]. Aus diesen Gründen ist das primä-re Ziel der Reanimationsausbildung das Training von Laien in CPR.…”
Section: Trainingsstrategien Für Die Basismaßnahmenunclassified
“…Es ist allgemein anerkannt, dass Ersthelfer-CPR für das Überleben von Kreislaufstillständen außerhalb des Krankenhauses entscheidend ist. Thoraxkompressionen und frühe Defibrillation sind die Hauptdeterminanten des Überlebens beim außerklinischen Kreislaufstillstand, und es gibt Hinweise, dass sich mit Einführung von Laientrainings das 30-Tageund 1-Jahres-Überleben verbessert hat [906,907].…”
Section: Wer Und Wie Ist Zu Trainieren?unclassified
“…None of the patients in this study had a spontaneous return of circulation thus supporting literature reporting poor survival rates in out of hospital pediatric cardiac arrests. [1][2][3] This study reported the rate of CPR bring provided to pediatric patients in cardiac arrest with a known history of chronic illness compared to those without. The comparison discovered patients with a history of chronic illness, such as cerebral palsy with complications, congenital heart disease and arrhythmias, were less likely to receive CPR than healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…Though uncommon, pediatric out of hospital cardiac arrests have a poor rate of survival and negative neurological outcomes for those that do survive. 2,3 Common causes of out of hospital cardiac arrest in pediatric patients were reported as sudden infant death syndrome, trauma and respiratory arrest. 2,4 Cardiac causes have been reported as the more common cause for out of hospital pediatric cardiac arrests, though it is uncommon to have an identifiable cause of cardiac arrest during the initial phase of resuscitation.…”
mentioning
confidence: 99%
See 1 more Smart Citation